2015
DOI: 10.1002/lno.10056
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of biased sex ratio at birth in a calanoid copepod

Abstract: To test the hypothesis that the sex ratio of the copepod Acartia tonsa is biased at birth, adult sex ratios of the offspring of families (21 families in 2011 and 72 in 2013) produced by field-caught females were determined in the laboratory under controlled conditions. Sex ratios at birth were estimated from the adult sex ratio, and after applying a correction in which all dead/missing individuals were counted as the rarer sex (males). Before correction the overall population sex ratio was female biased during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Our general conclusion is that for the C. helgolandicus CV stage, a 1 : 1 ratio may be generally valid. We note however, that Conover () found that the sex ratio of Calanus CVs, based on the appearance of the gonad, was strongly skewed toward females, and more recent evidence reported a female‐skewed sex ratio at birth in the calanoid copepod Acartia tonsa (Burris and Dam ), therefore, this assumption may need to be reviewed as new data come to light. Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our general conclusion is that for the C. helgolandicus CV stage, a 1 : 1 ratio may be generally valid. We note however, that Conover () found that the sex ratio of Calanus CVs, based on the appearance of the gonad, was strongly skewed toward females, and more recent evidence reported a female‐skewed sex ratio at birth in the calanoid copepod Acartia tonsa (Burris and Dam ), therefore, this assumption may need to be reviewed as new data come to light. Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 93%
“…14 and 15); however, we have not employed these here since we would have to assume that these recruitment trends perpetuate through all the developmental stages. We suggest that this is very unlikely to occur, especially as both experimental and field studies have shown cohorts to become less distinct and more spreadout over subsequent developmental stages (Campbell et al 2001; McKinnon and Duggan 2003; Table 2. Bêlehr� adek functions applied in this study to determine C. helgolandicus stage-specific development times (D, h).…”
Section: Vertical Life Table Mortality Rate Calculationsmentioning
confidence: 90%